Is hyperlinking to decryption software illegal?. - Cherry, S.M (IEEE spectrum)
Is a computer program a form of speech, protected in the United States under the First Amendment of its Constitution, or is it a device? In a case now under appeal, a federal court in New York City ruled that so called DeCSS software computer code that breaks the encryption scheme of DVDs - while deemed speech of a sort, does not merit the constitutional protection afforded to "pure expression." The federal court agreed with the case's movie-industry plaintiffs that DeCSS "accomplishes a mechanical task," and so resembles a device and is not protected. The court went even further: hyperlinks to pages with the DeCSS code may in some cases not be constitutionally protected speech and could be prohibited from being implemented. The plaintiffs in the case, eight movie studios, belong to an industry trade group, the Motion Picture Association of America, in Encino, Calif. The studios sued 2600, a quarterly magazine for hackers, for publishing the DeCSS code on its Web site and linking to other pages that also displayed the DeCSS code. The suit asked that 2600 be enjoined from both activities. The studios are concerned that code like DeCSS renders their encryption scheme ineffective, and that illegal copying and distribution of digital movies could become widespread